2019
DOI: 10.3390/su11205583
|View full text |Cite
|
Sign up to set email alerts
|

Does Herding Bias Drive the Firm Value? Evidence from the Chinese Equity Market

Abstract: Equity markets play a pivotal role in the sustainability of developing countries, such as China. The literature on the detection of herding biases is confined to the aggregate level (firms, sector/industry and market). The present study adds to the behavioral finance literature by addressing the surprisingly unnoticed phenomena of the behavioral impact of herding bias on firm value (FV) at the firm level, using the sample of A-Shares listed firms at the Shanghai and Shenzhen Stock Exchanges (SSE and SZSE) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…If a country wants to upgrade its sovereign rating, it should focus on minimizing external debt and maximizing foreign reserves [60]. Given the pivotal role the financial system plays in the sustainability of developing countries [2,50,54] and the equally critical sustainable role of CR agencies and announcements, it is worthwhile to understand the short-run and long-run asymmetries the CR brings to the macroeconomic environment. The asymmetric framework of [56] is very useful to look beyond the linear setting, while its capability to gauge the asymmetric (both positive and negative) nature of the relationship would be beneficial for policy actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a country wants to upgrade its sovereign rating, it should focus on minimizing external debt and maximizing foreign reserves [60]. Given the pivotal role the financial system plays in the sustainability of developing countries [2,50,54] and the equally critical sustainable role of CR agencies and announcements, it is worthwhile to understand the short-run and long-run asymmetries the CR brings to the macroeconomic environment. The asymmetric framework of [56] is very useful to look beyond the linear setting, while its capability to gauge the asymmetric (both positive and negative) nature of the relationship would be beneficial for policy actions.…”
Section: Discussionmentioning
confidence: 99%
“…Such sustainable development is somewhat linked with the stability of financial markets through the output credit risk of particular debt securities, and the dispersion of credit information to market investors. Financial markets play a pivotal role in the sustainability of developing countries [2]. A CR agency considers the capacity of a defaulter, generally a firm, a business, or a government capability to meet interest payments on their debt, and the contingency of omission.…”
Section: Introductionmentioning
confidence: 99%
“…When some companies in the same industry (especially leading companies) increase their level of debt, it can have a positive spill-over effect on the capital structure of other companies in the same industry, resulting in the companies in that industry competing to increase their level of debt and increasing the systemic risk of debt default within the industry. In this case, herd deviation exists at the industry and company levels [ 15 ]. Leary and Roberts [ 16 ] studied corporate financial decision-making and found that corporate financial decision-making can be significantly affected by peer companies and that peer effects are the largest factor affecting corporate financial decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture, food manufacturing, footwear production, and fuel processing also display herd pattern in the Chinese equity markets (Shah, Khan, Meyer, Meyer,& Oláh, 2019). The research on European countries using high frequency sample period data also report herding for sectors such as consumer goods, industrial and utilities, and healthcare (Andrikopoulos, Kallinterakis, Ferreira,& Verousis, 2017).…”
Section: Studies On Herding At Sector Levelmentioning
confidence: 94%